Clinical evaluation of direct short-fiber reinforced composite resin restorations and glass-ceramic endocrowns in endodontically treated molars : a 4-year follow - Myyryläinen, Tiina; Karsila, Ville (My University, 2019)
Aims The advances in adhesive dentistry have brought new treatment approaches for restoring endodontically treated teeth. The aim of this study was to compare the clinical outcome of direct short-fiber reinforced composite (SFC) restorations and indirect ceramic onlays (endocrowns) in restoring endodontically treated molars (ETM). On average, the follow up time was 4 years. Methods Eighteen ETM were randomly divided into two groups, first group received direct composite resin restorations with a SFC base (everX posterior, GC Corporation) (n=11) and second group received indirect glass-ceramic endocrowns (IPS Empress CAD, Ivoclar Vivadent AG) (n=7). Restorations were prepared in the student clinic of the Turku City Welfare division between November 2012 and January 2016. The restorations were evaluated at baseline and after 4.0 years for anatomical form, marginal adaptation, color match, surface texture, gingival inflammation, secondary caries, occlusal contacts and patient satisfaction. Plaque index and bleeding on probing were recorded and probing pocket depth measured. Results One endocrown was lost due to endodontic complications and one SFC restorations due to secondary caries, resulting in a 4-year survival rate of 85.7% and 90.9% for endocrown and SFC restorations respectively. One endocrown (14.3%) required occlusal adjustment, whereas four (36.4%) SFC restorations showed technical or biological complications needing maintenance. The causes for these complications were fractures of the veneering composite and secondary caries. Endocrowns showed better surface texture and anatomic morphology than SFC restorations. Although SFC restorations needed more maintenance, they still required less chair-time than endocrown restorations. Conclusions In general, both restoration types showed acceptable results. When compared to endocrowns, direct restorations with SFC base provide inexpensive and widely available alternative for restoring ETM. Even though SFC restorations might require more maintenance, they are simple to produce, need usually only one visit and repairs are usually minor and easy to perform.